Die finnische Kinder- und Jugendliteratur und ihre Präsens in Polen - Mrozewicz, Bolesław (Folia Scandinavica Posnaniensia, 2007)
In the article the authors presented the chosen aspects of the works of Katri Vala, one of the most interesting Finnishspeaking poets in the 1920s and 30s. She was part of the Nuori voima (Youth power) group, formed by young Finnish poets and writers, and later of the Tulenkantajat (The Torch Bearers). Her early poems are marked by the modernist tendencies which prevailed in the Sweedish-language poetry in Finland, foremost in the works of Edith Sodergran. The new way of writing, which Katri Vala perceived as something natural and coming from her heart, was never difficult for her and she never elaborated on it in theory. The poems written by Katri Vala are considered to be a modernist breakthrough in the poetry written in Finnish. The author, however, did not strive to substitute the whole of the Finnish writing until then, but rather to gain an equal status for the new poetry. Her attempt, as well as those of her colleagues, was unsuccessful in the 1920s and 30s.